The Role of Stovia in Education in Indonesia - Sarah Aisyah Salsabilah; Daiyatul Millah; Dzikri Rizki Cahya Aulia (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2023)
The purpose of this study is to find out the role of STOVIA in education in Indonesia. The research methods used are historical methods that include heuristics, source criticism, interpretation, and historiography.With the western education system makes society more advanced, and can not be prevented by the Dutch colonial government. The backwardness and stupidity that occurs in society is the result of invaders that are not easy to solve. The urgent need at that time made the Dutch East Indies government establish schools in the colonies, one of which was a medical school. As for the establishment of medical schools to overcome health problems that plague the indigenous population. Sekolah Dokter Jawa was founded on January 1, 1851 which later in further development was renamed School Fit Opleiding van Indische Artsen (STOVIA). Although initially the Javanese Medical School or STOVIA was established solely because of the needs of skilled and cheap health workers as well as the reluctance of Dutch doctors in overcoming the outbreak that occurred on the Java island. But we cannot deny if the establishment of the Javanese Medical School or STOVIA is the initial foundation of medical education in Indonesia.